The modern law of contract - Stone, Richard (Milton Park, Abingdon, Oxon : Routledge, 2011)
'The Modern Law of Contract is a clear and logical introduction to contract law, written by a leading author and lecturer with over thirty years of teaching and examining experience in the subject. Meticulously updated to include all of the recent developments and case decisions in the field, The Modern Law of Contract offers a contemporary overview of each of the key topics found on an undergraduate or GDL contract law module, making it the ideal introduction for students encountering the subject for the first time. Key learning features include: - boxed chapter summaries, which help to consolidate learning and understanding - additional'For thought' think points throughout the text where students are asked to consider'what if' scenarios - a fully revised set of diagrams to illustrate principles and facilitate the understanding of concepts and interrelationships -'Key Case' close-ups designed to help students identify key cases within contract law and improve their understanding of the facts and context of each case Clearly written and easy to use, The Modern Law of Contract enables undergraduate students of contract law to fully engage with the topic and gain a profound understanding of this pivotal area'--
Keywords: Contracts -- England; Contracts -- Wales